"Adults at risk": "vulnerability" by any other name?. Issue 1 (12th February 2018) - Pritchard-Jones, Laura
Abstract : Purpose: The purpose of this paper is to explore and critique the conceptual and terminological shift – particularly from "vulnerability" to "adult at risk" – in adult safeguarding under the Care Act 2014 and the Social Services and Well-being (Wales) Act 2014. Design/methodology/approach: The paper compares the notion of the vulnerable adult in safeguarding, with the notion of an adult at risk under the Care Act 2014 and the Social Services and Well-being (Wales) Act 2014 and questions to what extent such a shift addresses existing criticisms of "vulnerability". Findings: The paper criticises the notion of the "vulnerable adult" for perpetuating the stigma associated with an impairment or disability, and for the types of legal and policy responses deemed appropriate under such an understanding of vulnerability. While efforts to replace the term "vulnerable adult" with "adult at risk" are, to some extent, to be welcomed, "adult at risk" under the legislation relies on the same characteristics for which the "vulnerable adult" has been criticised. Nevertheless, the safeguarding provisions under the two Acts have made some strides forward in comparison to their legal and policy predecessors and the notion of the "vulnerable adult". Originality/value: This paper's originality and value lie in its scrutiny of the notion of "vulnerability" in adult safeguarding, in comparison to the newer terminology of an "adult at risk", whilst also suggesting that in important respects – in relation to the interventions deemed appropriate where an adult is perceived to be at risk – the two pieces of legislation are a marked improvement on their predecessors. It also offers some thoughts as to how criticisms of the new legislation may be overcome.